2008
DOI: 10.2137/145960610791015096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of birch tar oils on soil organisms and plants

Abstract: The use of birch tar oil (BTO) is a new innovation in plant and animal protection working against various weeds, harmful insects and rodents. Due to its novelty as a biocide/repellent/plant protection product, no comprehensive information on the effects of BTO on non-target soil organisms is available. In this study we examined the impact of BTO on non-target soil organisms (enchytraeids, nematodes and soil microbes) and plants using laboratory toxicity tests and field experiments. In addition, we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…To conclude, our studies give strong evidence on the potential of BTOs to be applied as an effective, non-costly, easy-to-use, and an environmentally friendly (Hagner et al 2010a(Hagner et al , 2010b) method against molluscs. As biological plant protection methods are needed to compensate for the potentially harmful and decreasing range of chemical molluscicides, this method could be a useful contribution as an alternative pest management strategy not only in home gardens, but also to some extent in organic farming practices and IPM strategies.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To conclude, our studies give strong evidence on the potential of BTOs to be applied as an effective, non-costly, easy-to-use, and an environmentally friendly (Hagner et al 2010a(Hagner et al , 2010b) method against molluscs. As biological plant protection methods are needed to compensate for the potentially harmful and decreasing range of chemical molluscicides, this method could be a useful contribution as an alternative pest management strategy not only in home gardens, but also to some extent in organic farming practices and IPM strategies.…”
Section: Discussionmentioning
confidence: 57%
“…Biological control using the nematode Phasmarhabditis hermaphrodita Schneider (Nematoda: Rhabditidae), has been successfully used, not only against slugs (Grimm 2002), but also to some extent against snails (Coupland 1995). Grimm (2002) and Speiser et al (2001) This study is part of a larger research programme in which the effects of BTO as a molluscicide (the current study) and their ecotoxicological effects on both terrestrial (Hagner et al 2010a) and aquatic (Hagner et al 2010b) organisms were investigated. Here we aimed at 1) studying the toxic effect of BTO on populations of A. arbustorum in the laboratory by direct spray application, 2) exploring the efficacy of the distillate to repel A. arbustorum outdoors when painted on a Perspex ® fence, and 3) demonstrating the repelling effect (and duration) of a BTO barrier in a field with a high frequency of A. lusitanicus.…”
Section: Introductionmentioning
confidence: 99%
“…Official data proving environmental impacts must be obtained for every product from laboratories which have an official quality system. Scientific evidence has proved that birch tar oil is an environmentally friendly product (Hagner et al 2010a(Hagner et al , 2010b. Similarly, it has been shown that essential oils do not pose any threat to the environment (Misra & Pavlostathis 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Many kinds of wood rotting fungi were growing on the untreated cut surface (right) but not on the treated surface. Hagner et al (2010a) reported that the risk to the soil environment caused by birch tar oil (concentration 500-1360 L/ha) is insignificant and short-term compared to many synthetic plant protection products. A proper dose of the pyrolysis liquid when sprayed on the soil surface activated soil organisms shortly after the application (Figure 11).…”
Section: Use Of Pyrolysis Liquids As a Fungicidementioning
confidence: 99%
“…Hagner et al [71] concluded that a birch tar oil (a mixture of wood vinegar and birch tar) showed no consistent, direct negative effects on enchytraeid worms, nematodes or soil microbial biomass when used at concentrations between 500-1360 L ha 1 . Instead, 100% birch tar oil (500 1360 L ha 1 ) showed a positive effect on microbial activity immediately after application, suggesting that readily utilized substances in the oil were rapidly consumed by microbes.…”
Section: Ecotoxicologymentioning
confidence: 99%